Cardiomyopathy: Genetics, Diagnosis, and Treatment - Sinclair, Heather Q. (MD Conference Express, 2010)
Arrhythmogenic right ventricular cardiomyopathy (ARVC), an inherited myocardial disorder, is associated with arrhythmias, heart failure, and sudden death [Syrris P et al. Am J Hum Genet 2006; Yang Z et al. Circulation Res 2006]. Clinical diagnosis of ARVC can be complicated, because multiple diagnostic tests are required and clinical presentation varies. This article discussed the etiology of ARVC and recent breakthroughs concerning detection, as well as the issue of hypertrophic cardiomyopathy.